Exploring attitudes and beliefs towards implementing cattle disease prevention and control measures: a qualitative study with dairy farmers in Great Britain - Brennan, Marnie L.; Wright, Nick; Wapenaar, Wendela; Jarratt, Susanne; Hobson-West, Pru; Richens, Imogen Frances; Kaler, Jasmeet; Buchanan, Heather; Huxley, Jonathan; O’Connor, Heather M. (MDPI, 2016)
Disease prevention and control practices are frequently highlighted as important to ensure the health and welfare of farmed animals, although little is known as to why not many practices are carried out. The aim of this study was to identify the motivators and barriers of dairy cattle farmers towards the use of biosecurity measures on dairy farms using a health psychology approach. Twenty-five farmers on 24 farms in Great Britain (GB) were interviewed using the Theory of Planned Behaviour framework. Results indicated that farmers perceived they had the ability to control what happened on their farms in terms of preventing and controlling disease, and described benefits from being proactive and vigilant. However, barriers were cited in relation to testing inaccuracies, effectiveness and time-efficiency of practices, and disease transmission route (e.g., airborne transmission). Farmers reported they were positively influenced by veterinarians and negatively influenced by the government (Department for Environment Food & Rural Affairs (DEFRA)) and the general public. Decisions to implement practices were influenced by the perceived severity of the disease in question, if disease was diagnosed on the farm already, or was occurring on other farms. Farmers described undertaking a form of personal risk assessment when deciding if practices were worth doing, which did not always involve building in disease specific factors or opinions from veterinarians or other advisors. These results indicate that further guidance about the intricacies of control and prevention principles in relation to specific animal diseases may be required, with an obvious role for veterinarians. There appears to be an opportunity for farm advisors and herd health professionals to further understand farmer beliefs behind certain attitudes and target communication and advice accordingly to further enhance dairy cattle health and welfare.